Recovery from prolonged exercise: Restoration of water and electrolyte balance - Maughan, R. J.; Shirreffs, S. M. (Journal of Sports Sciences, 1997)
Rapid and complete restoration of fluid balance after exercise is an important part of the recovery process, especially in hot, humid conditions, when sweat losses may be high. Rehydration after exercise can only be achieved if theelectrolytes lost in sweat, as well as the lost water, arereplaced. However, the amount of electrolytes lost in sweat is highly variable between individuals and although the optimum drink may be achieved by matching drink electrolyte intake with sweat electrolyte loss, this is virtually impossible in sport settings. The composition of sweat varies considerably not only between individuals, but also with time during exercise and it is further influenced by the state of acclimatization. A moderate excess of salt intake would appear to be beneficial as far as hydration status is concerned, without any detrimental effects on health, provided that fluid intake is in excess of sweat loss and that renal function is not impaired. To achieve effective rehydration following exercise in the heat, the rehydration beverage should contain moderately high levels of sodium (at least 50 mmol l-1), and possibly also some potassium. The addition of substrate is not necessary for rehydration, although a small amount of carbohydrate (<2%) may improve the rate of intestinal uptake of sodium and water. The volume of beverage consumed should be greater than the volume of sweat lost to providefor the ongoing obligatory urine losses. Therefore, the palatability of the beverage is important. Many individuals may lose substantial amounts of sweat and will therefore have to consume large amounts of replacement fluids and this is more likely to be achieved if the taste is perceived as being pleasant. Water alone is adequate for rehydration purposes when solid food is consumed, as this replaces the electrolytes lost in sweat. However, there are many situations where intake of solid food is not possible or is deliberately avoided and, in these instances, the inclusion of electrolytes in rehydration beverages is essential. Where a second exercise bout has to be performed, replacement of sweat losses is an essential part of the recovery process. Exercise performance will be impaired if complete rehydration is not achieved.